Informed consent in dementia research: how Public Involvement can contribute to addressing “old” and “new” challenges - Diaz, Ana; Birck, Cindy; Bradshaw, Angela; Georges, Jean; Lamirel, Daphne; Moradi-Bachiller, Soraya; Gove, Dianne (Frontiers in Dementia, 2025)
Informed consent is a critical ethical requirement in research, ensuring the protection of participants' rights and promoting their wellbeing and autonomy. In dementia research, this process becomes particularly complex due to cognitive impairments and fluctuating capacity. While substantial work has been done to address these challenges, much of the literature on informed consent in dementia research has been shaped by the perspectives of researchers and healthcare professionals, with less focus on those with lived experience. This paper provides an overview of the perspectives of people with dementia and their carers resulting from Public Involvement activities organized by Alzheimer Europe. It builds on Alzheimer Europe's previous work with the European Working Group of People with Dementia and draws on discussions held during a face-to-face meeting about Participant Informed Consent forms and processes used in two specific European projects. We highlight views and key concerns raised by people with lived experience regarding the informed consent process, including barriers and facilitators. In addition to ensuring understandability, the discussions emphasized the importance of promoting respect and autonomy, ensuring that the values and interests of people with lived experience remain central throughout the research process. This paper contributes to the ongoing dialogue on improving informed consent practices in dementia research, highlighting the need for continuous involvement and the inclusion of people with lived experience in shaping consent practices to address both old and emerging challenges (i.e., new types of research such as artificial intelligence and data sharing/re-use) in dementia research.